(untitled) (Research, Society and Development, 2021)
Computational Thinking (CT) is a strategy used in the teaching/learning process, involving problem solving, in order to develop critical and creative thinking, autonomously, interdisciplinaryly. This article presents a reflexive analysis on the theme, based on literatures that address CT and its consequences. It aims to discuss the benefits of the development of CT in basic education, as well as briefly describe some strategies already in use so that the CT can be taught, thus benefiting students, teachers and society. We conclude that when developing the CT the student becomes a subject constructor of knowledge, in a critical, creative, versatile, flexible and innovative way, and that this can happen through various strategies, whether through the teaching of robotics, block programming, digital narratives, games, with activities without the use of technologies, or in a transversal way within the disciplines.